Effects of sulfate and magnesium on cement degradation under geologic CO2 sequestration conditions. (August 2017) - Guo, Jilong; Cao, Bo; Steefel, Carl I.; Chen, Jiawei; Hu, Yandi
Highlights: Effects of sulfate and magnesium on cement degradation were investigated under GCS conditions. First time observation of gypsum formation on cement reacted under relevant GCS condition. The formation of gypsum was due to low solution pH and a low liquid-to-solid ratio. Gypsum coating on cement surface can protect cement from further CO2 attack. Abstract: For safer geologic CO2 sequestration (GCS), it is important to understand CO2 -brine-cement interactions, which affect wellbore integrity. However, potential effects of sulfate and magnesium ions on cement degradation under GCS conditions are not well understood. Here Class H Portland cement were reacted in brines containing 0.05 M sulfate and/or magnesium ions under both GCS (50 °C and 100 atm CO2 ) and control (50 °C and atmospheric pressure) conditions. Using optical microscopy and scanning electron microscope coupled with energy dispersive spectrometry and electron back scattered electron (SEM-EDS/BSE), slower cement carbonation rates were observed in the presence of sulfate under GCS conditions, because of gypsum precipitation on cement surfaces. Calcite rather than gypsum formed in both the inner layers of cement samples reacted under GCS conditions, and on cement surfaces reacted under atmospheric pressure conditions. Under GCS conditions, the dissolved CO2 lowered the pH of the solution surrounding cement surfaces, thus favoring the formation of gypsum over calcite on cement surfaces; while the high pH condition in pore solution inside cement favors the formation of calcite over gypsum. The presence of magnesium had no significant effect on cement degradation under GCS conditions, as brucite, magnesium carbonates and magnesium calcite did not form, due to the low pH at cement surface and the limited diffusion of Mg into cement inner layers.